Enteral Lactoferrin Supplementation for Preventing Sepsis and Necrotizing Enterocolitis in Preterm Infants: A Meta‑Analysis With Trial Sequential Analysis of Randomized Controlled Trials - Gao, Ya; Hou, Liangying; Lu, Cuncun; Wang, Qi; Pan, Bei; Wang, Quan; Tian, Jinhui; Ge, Long (Frontiers in Pharmacology, 2020)
Background: Several clinical trials investigated the effects of enteral lactoferrin supplementation on the prevention of sepsis and necrotizing enterocolitis (NEC) in preterm infants, but the efficacy and safety remain disputed. Therefore, we systematically evaluated the effect of enteral lactoferrin supplementation in preterm infants through a meta‑analysis with trial sequential analysis (TSA). Methods: We searched six databases to identify randomized controlled trials (RCTs) that evaluated the effects of lactoferrin supplementation compared with placebo or no intervention in preterm infants. RevMan version 5.3 software was used to estimate pooled relative risks (RRs) with the random-effects model. TSA, subgroup analyses, and meta-regression analysis were also performed. Results: Nine RCTs with 3515 samples were included. With low to moderate quality of evidence, compared with placebo, enteral lactoferrin supplementation did not significantly decrease the incidences of late-onset sepsis (RR=0.63, 95%CI: 0.38 to 1.02, P=0.06), NEC stage II or III (RR=0.68, 95%CI: 0.30 to 1.52, P=0.35), all-cause mortality (RR=0.89, 95%CI: 0.51 to 1.57, P=0.69), bronchopulmonary dysplasia (RR=1.01, 95%CI: 0.90 to 1.13, P=0.92), retinopathy of prematurity (RR=0.80, 95%CI: 0.49 to 1.32, P=0.38), invasive fungal infection (RR=0.27, 95%CI: 0.02 to 3.94, P=0.34), intraventricular hemorrhage (RR=1.40, 95%CI: 0.39 to 5.08, P=0.61), and urinary tract infection (RR=0.35, 95%CI: 0.11 to 1.06, P=0.06). Subgroup analysis revealed that lactoferrin significantly reduced the incidence of sepsis in infants with a birth weight below 1500g (RR=0.43, 95%CI: 0.22 to 0.84, P=0.01). TSAs of the primary outcomes showed that the evidence is insufficient and further data is required. Conclusions: Limited evidence suggested that enteral lactoferrin supplementation was associated with a reduction of late-onset sepsis in infants with a birth weight below 1500g, however, did not decrease the incidence of NEC stage II or III, all-cause mortality, and other adverse events in preterm infants. The present evidence was insufficient to inform clinical practice.